Relevansi Pemikiran Pluralisme Gus Dur di Era Digital: Tinjauan Keberagaman dalam Perspektif Pendidikan Kewarganegaraan - Aliya Zulva Ahsani; Fadhil Gilland Rahmatullah; Nabiha Ayu Mardhatillah; Moh. Faizin (Jurnal Teologi Islam, 2026)
This study looks into how relevant K.H. Abdurrahman Wahid's (Gus Dur's) ideas on pluralism are for responding to these modern challenges, especially from the viewpoint of Civic Education (PPKn). The research uses a literature review, pulling data from academic journals, books, and other related documents. It focuses on three main questions: (1) How Gus Dur's life experiences formed his pluralistic outlook; (2) How diversity and pluralism are understood within Civic Education; and (3) Which specific parts of Gus Dur's pluralism can be used in today's digital world. The findings show that Gus Dur's thinking—especially on universal humanism, the "indigenization of Islam," and his concept of separating religion and state (though not complete secularism)—provides a strong basis for building a new digital citizenship. This new ethical framework is meant to encourage attitudes that are tolerant, critical, and open, all of which reflect the core values of Pancasila.